Introduction: Transforming Cities: Urbanization and International Development in Africa and Latin America since 1945 - Frey, Mark; Kunkel, Sönke; Kwak, Nancy (Comparativ, 2020)
This introduction makes a case for a more forceful dialogue between historians of development and global urban historians. Global processes of urbanization, it argues, have long been an im- portant concern for development actors, but historians have only recently begun to explore the meaning and role of urban spaces within international development. The article suggests that a look at the history of urban development policies provides a better understanding of space as an object and context of development. It also claims that a new research focus fosters new insight into the transnational agency of architects and city planners. Last, it sheds new light on the ways in which development became big business in the post-1945 world.